Attentional bias in snus users: an experimental study. - Rune Aune Mentzoni; Bjørn Sætrevik; Helge Molde; Nora Wiium; Jørn Hetland; Ida Fagerland; Linn Tinnesand Nordnes; Sunniva Straume Storemark; Ingrid Nesdal Fossum; Ståle Pallesen (PLoS ONE, 2014)
The use of nicotine in the form of "snus" is substantial and increasing in some geographic areas, in particular among young people. It has previously been suggested that addictions may operate through a mechanism of attentional bias, in which stimuli representative of the dependent substance increase in salience, thus increasing the addictive behavior. However, this hypothesis has not been tested for the case of snus. The current experiment used a modified Stroop task and a dot-probe task to investigate whether 40 snus users show an attentional bias towards snus-relevant stimuli, compared to 40 non-snus users. There were no significant differences between the two groups on reaction times or accuracy on either Stroop or dot-probe task, thus failing to show an attentional bias towards snus-relevant stimuli for snus users. This could imply that other mechanisms may contribute to maintenance of snus use than for other addictions. However, this is the first experimental study investigating attentional bias in snus users, and more research is warranted.